A Estratégia da Posição do Antecedente em línguas românicas de sujeito nulo - Fiéis, Alexandra; Madeira, Ana; Teixeira, Joana (Revista da Associação Portuguesa de Linguística, 2022)
This study investigates the interpretation of pronominal subjects in European Portuguese, Spanish and Italian. 30 native speakers of each language completed two multiple-choice tasks (speeded and untimed), which elicited their interpretation of null and overt subject pronouns in intrasentential contexts with the order matrix‑subordinate. The tasks had a 2x2 design, crossing the following variables: animacy of the matrix object (+ animate vs. - animate) and type of pronominal embedded subject (overt vs. null). Results indicate that the PAS is consistently followed in EP but not in Italian or Spanish. In these languages, this strategy is adopted in overt subject resolution only in contexts where the antecedents are [+ animate]. In the resolution of null subjects, Italian and Spanish exhibit optionality between subject and object antecedents. Hence, there is microvariation in the resolution of pronominal subjects in these languages. Possible reasons for this are discussed in detail.